A NEW LOOK AT THE BIOMARKER ROLE OF PROSTANOIDS – COMMON LINKS IN THE PATHOGENESIS OF UROLOGICAL CANCERS AND COVID-19 - Komarevtsev, V.N.; Balabanova, K.V.; Kalinin, I.V.; Komarevtseva, I.O.; Vyshnitska, I.A.; Shipilov, K.V.; Seryogina, N.M. (World of Medicine and Biology, 2024)
The purpose of the study was a comparative analysis of the level of eicosanoid excretion in urine in patients with COVID-19 and tumors of the kidneys, bladder and prostate gland, which, in our opinion, will make it possible to establish some common links in the pathogenesis of tumor lesions and COVID-19. Urinary excretion of PGI2, PGE2, TxB2, PGF2α in patients with COVID-19 , as in patients with bladder cancer and prostate cancer is significantly increased. Whereas in patients with kidney cancer without and with metastases, the entire spectrum of prostanoids was significantly reduced. The leading prostanoids in COVID-19 patients were prostacyclin PGI2 and PGE2; in patients with bladder cancer and prostate cancer – PGE2, and in patients with kidney cancer without and with metastases – thromboxane B2.